If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3 + -2x) + 4 = -7 (3 * -2 + -2x * -2) + 4 = -7 (-6 + 4x) + 4 = -7 Reorder the terms: -6 + 4 + 4x = -7 Combine like terms: -6 + 4 = -2 -2 + 4x = -7 Solving -2 + 4x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4x = -7 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = -7 + 2 4x = -7 + 2 Combine like terms: -7 + 2 = -5 4x = -5 Divide each side by '4'. x = -1.25 Simplifying x = -1.25
| [31]=3w+9-8w | | 6(x+2)=65 | | 30+4x= | | (2-3k)x^2+(4-k)x+2= | | 4x+2y=108 | | y=4x^3-3x-2 | | 8s= | | r+4= | | 14.73=-24.23-6.8b | | r+n= | | 15x-10+21x+7=-9-3x+16+x | | 22x+23-17x-16=x-8+2x+27 | | X(1+x)(3-x)=3 | | (x^2d^2-3xd+4)y=x+x^2*lnx | | (x+5)*(x+5)=1280 | | 8-p=1 | | n^3-3n^2+2n-60=0 | | (x+5)*(x+5)*(x+5)=1280 | | 18x+15-15x+26=-4+7+9x+6 | | 12-3(-4-2y)=-5 | | 18x+15+15x+26=-4+7+9x+6 | | 6-5=2 | | 5+8i=0 | | y=tan(6x) | | 12+13=x | | -7-13z+15+16z=57-5z+4z-52 | | (2x-1)(3x-2)=33 | | 3x+14+6x-29=43+8x-70-32 | | 3x+14+6x-29=m-3+4m-4 | | 12m+6n-6m+10n= | | 10m+12-4m-19=m-3+4m-4 | | (3x+y^2+2y^5)dx+(2x^2y+5xy^4)dy=0 |